Ecological construction status of photovoltaic power plants in China’s deserts - Wang, Yimeng; Liu, Benli; Xing, Yu; Peng, Huaiwu; Wu, Hui; Zhong, Jianping (Frontiers in Environmental Science, 2024)
Solar photovoltaic (PV) is one of the most environmental-friendly and promising resources for achieving carbon peak and neutrality targets. Despite their ecological fragility, China's vast desert regions have become the most promising areas for PV plant development due to their extensive land area and relatively low utilization value. Artificial ecological measures in the PV plants can reduce the environmental damage caused by the construction activity and promote the ecological condition of fragile desert ecosystems, therefore yield both ecological and economic benefits. However, the understanding of the current status and ecological benefits of this approach in existing desert PV plants is limited. Here we surveyed 40 PV plants in northern China's deserts to identify the ecological construction modes and their influencing factors. We quantified the ecosystem service value (ESV) provided by these PV plants using remote sensing data and estimated the potential for ESV enhancement. Our results show that PV plant construction in desert regions can significantly improve the ecosystem, even with natural restoration measures (M1) alone, resulting in a 74% increase in average fractional vegetation cover (FVC) during the growing season, although the maximum average FVC of only about 10%. The integrated mode M4, which combined artificial vegetation planting M2 and sand control measures M3, further enhance the average growing season FVC to 14.53%. Currently, 22.5% of plants lack ecological measures, 40% employ only a single measure, but 92% of new plants since 2017 have adopted at least one ecological construction mode. The main influencing factors include surface type, policy support, water resources, ecological construction costs, and scientific management guidance. If artificial ecological construction were incorporated, a significant ESV could be achieved in these PV plants, reaching $8.9 million (a 7.7-fold increase) if assuming a targeted 50% vegetation coverage. This study provides evidence for evaluating the ecological benefit and planning of large-scale PV farms in deserts.